1991
DOI: 10.1093/nar/19.7.1359
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic variation inTrypanosoma brucei: a telomeric expression site for variant-specific surface glycoprotein genes with novel features

Abstract: African trypanosomes evade the immune response of their host by periodically changing their variant surface glycoprotein (VSG) coat. Each coat is encoded by a separate VSG gene. Expressed genes are in a telomeric expression site (ES) and there are several sites in each trypanosome. To study the transcription control of VSG genes in Trypanosoma brucei we have analyzed an ES, called the dominant ES (DES), that readily switches off and on. The promoter area of the DES is very similar to that of the 221 ES (Zomerd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 58 publications
4
35
0
Order By: Relevance
“…Most sequences were present in 1-11 copies, except for G1, which was present in 30-40 copies. Because G1 is present in both FM162566 and FM162572 (33), and FM162566 is the active ES in this isolate, the relatively high proportion of this PCR product was in keeping with the higher transcription efficiency in the dominant ES (36) and with the more efficient processing of transcripts from the active ES (29). Here again, 11-17 outliers (12-19% of the total sequences) were generated.…”
Section: Resultsmentioning
confidence: 76%
“…Most sequences were present in 1-11 copies, except for G1, which was present in 30-40 copies. Because G1 is present in both FM162566 and FM162572 (33), and FM162566 is the active ES in this isolate, the relatively high proportion of this PCR product was in keeping with the higher transcription efficiency in the dominant ES (36) and with the more efficient processing of transcripts from the active ES (29). Here again, 11-17 outliers (12-19% of the total sequences) were generated.…”
Section: Resultsmentioning
confidence: 76%
“…The neo probe was the RsaI-BamHI restriction fragment containing the 3Ј end of the gene. The core ES promoter probe was a 315-bp HpaI-SalI fragment (positions 1359 to 1673 in the sequence described in reference 54) isolated from plasmid pRK8(ϩ) (52).…”
Section: Methodsmentioning
confidence: 99%
“…DNA rearrangements have been described to occur in the region upstream of the promoter, in a few ES inactivation events. Some of these rearrangements involved either the deletion of the upstream promoter, in an ES where the ES promoter, embracing a region of about 13 kb, was tandemly duplicated (18), or changes within the 50-bp repeat array upstream of the promoter (52). To determine the significance of these observations, we decided to search in detail, in panels of independent clones with consecutive on-off-on switches at a specific ES, for any DNA rearrangements that might occur consistently upon ES activation and inactivation.…”
mentioning
confidence: 99%
“…Lister 427 has 15 different B-ESs), usually carrying different VSGs, but all B-ESs have very similar genomic organization with ~90% sequence identity (Hertz-Fowler et al 2008). Earlier studies focused on B-ES promoters also showed that they are almost always identical (Pham et al 1996;Zomerdijk et al 1990Zomerdijk et al , 1991. Therefore, how T. brucei manages to fully express only one B-ES and VSG had been a great puzzle for more than a couple of decades.…”
Section: Rap1-mediated Silencing Is Essential For Monoallelic Expressmentioning
confidence: 99%